An investigation on girth friction welding of duplex stainless steel pipes. (March 2020) - Kanan, L.F.; Vicharapu, B.; Pissanti, D.R.; Kwietniewski, C.E.F.; Clarke, T.; De, A.
Highlights: Girth friction welding (GFW) can join linepipes in solid state by plastic deformation. A detailed investigation on GFW of duplex stainless steel linepipes is presented. A coupled temperature-displacement model is used to analyse experimental findings. Computed thermal cycle and material flow pattern corroborated well with measurements. Weld joint structure showed very little percentage of harmful intermetallic phase. Abstract: Girth friction welding is a novel technique to join co-axial linepipes with an external ring (girth) in solid state and without melting of materials. The ring or the girth is rotated between two pipes under an axial force resulting in frictional heat generation and plastic deformation along the pipe-girth interfaces. The rotation of the girth is stopped after a preset displacement of the pipes while the force is maintained to consolidate the deformed material and form the joint along the girth-pipe interfaces. Since the girth is only rotated and the pipeline sections remain stationary, the process simplifies the in situ assembly operations and enables the joining of complex configurations. As the melting of pipes and girth is avoided, the formation of harmful intermetallic compounds and deterioration of toughness in the heat affected zone are minimized. A comprehensive numerical model is reported in the present work to analyse the influence of key process variables on the rate of heat generation, resulting temperature field and thermal cycles, and the nature of material flow along the pipe-girth interfaces in girth friction welding of duplex stainless steel pipes. The computed results of thermal cycles and joint shapes are validated with the corresponding experimentally measured results. The results showed a favorable balance of the ferrite and austenite phases, and very little presence of the harmful sigma phases in the recrystallized weld-zone, which is difficult in fusion welding processes of similar materials.